ASSESSMENT OF CARBON SEQUESTRATION POTENTIAL OF TREES IN ADEOYO GENERAL HOSPITAL PREMISES, IBADAN, OYO STATE - Adenuga, D. A.; Agbo-Adediran, A. O.; Fadipe, O. B.; Afolabi, R. T.; Roberts, A. E.; Oyedeji, M. B.; Adetunji, A. S.; Eze, F. B. (FUDMA JOURNAL OF SCIENCES, 2024)
This study assessed the carbon sequestration of trees around healthcare facilities at Adeoyo General Hospital, Adeoyo, Ibadan. Total enumeration of all the trees in the study areas was carried out. Data were collected on dbh (cm) and total height (m) and these parameters were used to compute basal area (m2), volume (m3) and Carbon sequestered (ton). The parameters measured from the study area tree include: diameter at breast height (DBH), total height (H), basal area (B.A), Total volume (V). Trees species of 10cm Dbh and above were measured and enumerated. The carbon sequestration of 64 trees belonging to 13 species, 8 families was estimated using allometric equations. The results showed the growth characteristics of various tree species. Azadirachta indica dominated constituting 42.2% of the total population. Terminalia catappa and Gliricidia sepium are also significant. Mean diameter, height, basal area, and volume suggest a diverse forest with a wide range of tree sizes. The total carbon sequestered by these trees was 194425.2tCwith the average carbon sequestered of the trees as 3037.8947tC. The highest average of 8880.9tC sequestration was observed in Delonix regia and the lowest (44.1tC) in Ficus capensis. Delonix regia showed the highest DBH and more carbon sequestration potential, whereas Newbouldia laevis showed the minimum in both DBH and carbon sequestration potential.
Keywords: Forest carbon sequestration; Soil organic carbon; Climate change; Assessment; Adeoyo General Hospital; Organic carbon